High-flow oxygen therapy and non-invasive ventilation in extubated patients with COVID-19 and risk of reintubation - Munarriz-Ticona, Abraham (2023)
Introduction: High-flow oxygen therapy (HFO) and non-invasive ventilation (NIV) are non-invasive systems that are administered post-extubation in COVID-19 patients to avoid reintubation. However, the evidence on the choice of any of these devices is not very clear. The objective was to determine if the group that received OAF compared to the group that received NIV is associated with a lower risk of reintubation in adults with difficult weaning and extubated due to COVID-19. Material and methods: Retrospective cohort study in 206 records of patients in difficult weaning from mechanical ventilation in the Intensive Care Unit (ICU). The primary outcome was reintubation in patients who failed HFO or post-extubation NIV, and the secondary outcomes were ICU hospital stay and 90-day mortality. Results: Two hundred and six patients met the inclusion criteria, 102 patients in the OAF group and 104 patients in the NIV group. During the 72-h follow-up, the reintubation rate in the HFO group was higher [n=24 (64,9%)] compared to the NIV group [n=13 (35,1%)], showing in the analysis of Kaplan-Meier significant differences (Log-Rank-Test p=0,005). COX regression showed a higher risk of reintubation in the HFO group compared to NIV (HR 2,74; 95%CI 1,42-5,68; p=0,007). There were no differences in ICU hospitalization days (p=0,913) or in 90-day mortality (Log-Rank-Test p=0,49). Conclusion: This retrospective observational study suggested that HFO versus NIV was associated with a higher risk of reintubation, but not with 90-day mortality.